2018
DOI: 10.1111/ijfs.13921
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterisation of a novel agar oligosaccharide–iron (III) complex

Abstract: This study aimed to synthesise a complex of agar oligosaccharides (AOS) with ferric iron and to evaluate its physicochemical and structural characteristics. Based on single factor, Plackett-Burman and response surface optimal experiments of three factors at three levels, the optimised chelate conditions of the AOSiron (III) complex were mass ratio of AOS to iron ions of 4.5:1 g:g, reaction temperature of 74°C and reaction time of 60 min. Under these conditions, the iron content and total sugar content were 14.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…23 400 to 1000 cm À1 were characteristic peaks of iron core structure "b-FeOOH" of polysaccharide-iron(III) chelates. 24 In our study, the weak absorption peak of CP-1-Fe and CP-3-Fe at 450 and 850 cm À1 were observed, respectively. The absorption peak at around 1060 cm À1 in polysaccharide and polysaccharide-iron(III) was indicated the existence of a pyran-ring structure.…”
Section: Ft-ir Spectroscopysupporting
confidence: 55%
“…23 400 to 1000 cm À1 were characteristic peaks of iron core structure "b-FeOOH" of polysaccharide-iron(III) chelates. 24 In our study, the weak absorption peak of CP-1-Fe and CP-3-Fe at 450 and 850 cm À1 were observed, respectively. The absorption peak at around 1060 cm À1 in polysaccharide and polysaccharide-iron(III) was indicated the existence of a pyran-ring structure.…”
Section: Ft-ir Spectroscopysupporting
confidence: 55%
“…AOS-iron was synthesized as described previously. 26 The steps in the preparation of AOS-iron were as follows. First, 0.25 g AOS and 0.125 g sodium citrate were dissolved in 10 mL distilled water, and the pH was adjusted to 5.00 AE 0.05 with 1 mol L À1 HCl.…”
Section: Preparation Of Aos-iron Complexmentioning
confidence: 99%
“…Recent studies on polysaccharide–Fe(III) complexes indicated that the −OH and −COOH groups were bound to Fe 3+ . 24 , 37 , 38 Therefore, it was speculated that −OH and −COOH groups in the pectin chains acted as a bridge to connect Fe 3+ in the AP–Fe(III).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the AP–Fe (III) complex comprised a β-FeOOH structure, which was obtained by comparison with the standard spectrum. Recent studies on polysaccharide–Fe­(III) complexes indicated that the −OH and −COOH groups were bound to Fe 3+ . ,, Therefore, it was speculated that −OH and −COOH groups in the pectin chains acted as a bridge to connect Fe 3+ in the AP–Fe­(III).…”
Section: Resultsmentioning
confidence: 99%